2018
DOI: 10.1210/jc.2018-01372
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High Triglyceride Levels During Early Pregnancy and Risk of Preterm Delivery: A Retrospective Cohort Study

Abstract: Context Maternal obesity increases the risk of preterm delivery. Obesity is known to be associated with altered lipid metabolism. Objective To investigate the associations between high maternal triglyceride (mTG) levels during early pregnancy and risks of preterm delivery stratified by early pregnancy body mass index (BMI). Design Retrospective cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…We found concentrations for a set of TGs to be higher and some species of PCs to be lower in prenatal plasma from African American women with PTB compared to those with term birth ( Figure 2C). Our finding is consistent with other reports of high TG levels being associated with an elevated risk of PTB (Lin et al, 2018;Moayeri et al, 2017). Lower PC could be related to higher TG due to poor assembly of lipoproteins, but these findings need further investigation.…”
Section: Lipoproteins and Ptbsupporting
confidence: 93%
See 2 more Smart Citations
“…We found concentrations for a set of TGs to be higher and some species of PCs to be lower in prenatal plasma from African American women with PTB compared to those with term birth ( Figure 2C). Our finding is consistent with other reports of high TG levels being associated with an elevated risk of PTB (Lin et al, 2018;Moayeri et al, 2017). Lower PC could be related to higher TG due to poor assembly of lipoproteins, but these findings need further investigation.…”
Section: Lipoproteins and Ptbsupporting
confidence: 93%
“…Specifically, TG(53:5), TG(53:4), TG(54:5), TG(54:6), TG(52:6), and TG(52:4) were positively associated with PTB. Lin et al (2018) also reported that the higher TG levels they found were related to PTB in both overweight and normal-weight women, suggesting that the association is independent of BMI. PCs were found to be in lower levels with PTB and some TG species were found to be higher with PTB.…”
Section: Lipoproteins and Ptbmentioning
confidence: 79%
See 1 more Smart Citation
“…A retrospective study of 49,612 women concluded that high mTG levels during early pregnancy increased the risk of preterm delivery not only among women with overweight and obesity but also among women with normal BMIs. 7 Studies have suggested that high TG levels may be associated with an elevated risk of spontaneous preterm delivery in women. 31 Fetal imprinted genes may influence clinically relevant maternal circulating triglyceride concentrations early in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Supraphysiological levels of maternal lipids in early or late pregnancy have been shown to be associated with adverse pregnancy outcomes. In early pregnancy, elevated maternal TG (mTG) concentrations are associated with the prevalence rates of preterm birth, [5][6][7] large-for-gestational-age (LGA) newborns, 6 pregnancy-induced hypertension, 6,8 gestational diabetes mellitus (GDM), 9 and preeclampsia. 6,[10][11][12][13][14] In late pregnancy, elevated mTG concentrations are also related to the prevalence rates of pregnancyinduced hypertension, 15 preeclampsia, 11,13,15 GDM, intrahepatic cholestasis of pregnancy, and LGA newborns.…”
Section: Introductionmentioning
confidence: 99%